Pengaruh Disiplin Kerja dan Reward Terhadap Kinerja Karyawan di PT Aklab Nurse Call System Garut - Wifi Syari; Dody Hermana; Hedi Cupiadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The objective of this study is to analyze the influence of Work Discipline and Rewards on Employee Performance.The research utilizes primary data collected through questionnaires distributed to 35 respondents, who are employees of PT AKLab Nurse Call System in Garut. The sampling method employed is non-probability sampling with a purposive sampling technique. This study adopts a quantitative method with a descriptive and associative approach. Hypothesis testing is conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that both Work Discipline and Rewards have a significant partial effect on Employee Performance. The study concludes that effective implementation of Work Discipline and optimal provision of Rewards can enhance Employee Performance.